Sun sensitivity and sun protective behaviors during sun exposure among indoor office workers in the American Midwest. Issue 6 (25th June 2018) - Jung, Alesia M.; Dennis, Leslie K.; Jacobs, Elizabeth T.; Wondrak, Georg T.
Summary: Background/purpose: Sun sensitivity, a confounder between sun exposure and sun protection, is often overlooked. We examined how sun exposure and sun protection behaviors among indoor workers varied by sun sensitivity. Methods: Sun exposure and sun protection diaries over a 45‐day period from Midwestern United States indoor workers were examined. We categorized sun sensitivity (fair and non‐fair complexion) using tanning inability and sunburn tendency. Total exposure (sunrise to sunset) and peak exposure (10 am and 4 pm ) lasting at least 60 minutes were examined. Percentages of time using sun protection were reported. We determined associations between fair complexion, mean sun exposure, and mean sun protection times with logistic regression. Results: Fair individuals spent less time in the sun than non‐fair individuals, but a greater proportion of time using sun protection behaviors, including sunscreen with SPF 30+ (odds ratio (OR) = 1.36; 95% confidence interval (95% CI) = 0.98, 1.87)), or wearing long‐sleeved shirts (OR = 2.89; 95% CI = 1.24, 6.73). Conclusion: Fair individuals spent less time in the sun and practiced more sun protective behaviors than non‐fair individuals. This complex association between sun sensitivity, sun protection and sun exposure has not consistently been addressed in studies of skin cancer.